Arctic Terrestrial Biodiversity Monitoring Plan - Christensen, T.; Payne, J.; Doyle, M.; Ibarguchi, G.; Taylor, J.; Schmidt, N.M.; Gill, M.; Svoboda, M.; Aronsson, M.; Behe, C.; Buddle, C.; Cuyler, C.; et al. (Conservation of Arctic Flora and Fauna (CAFF), 2013)
"The CBMP Terrestrial Expert Monitoring Group (CBMP-TEMG) has developed the Arctic Terrestrial Biodiversity Monitoring Plan (CBMP-Terrestrial Plan/the Plan) as the framework for coordinated, long-term Arctic terrestrial biodiversity monitoring. The goal of the CBMP-Terrestrial Plan is to improve the collective ability of Arctic traditional knowledge (TK) holders, northern communities, and scientists to detect, understand and report on long-term change in Arctic terrestrial ecosystems and biodiversity." We gratefully acknowledge the funding provided by the Nordic Council of Ministers